2020
DOI: 10.24252/elties.v2i1.10269
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Word Chain Game on Increasing the Eighth Grade Students’ Vocabulary at MTS Barana Jeneponto

Abstract: The research aims at finding out the influence of Word Chain Game in increasing the students’ vocabulary with two research objectives.This research was conducted at MTs Barana Jeneponto Regency in Academic Year 2018/2019. In this research, the population was 60 students in the eighth grade. The sample was 40 students. There were 20 students in Class VIII A as experimental class and 20 students in VIII B as controlled class. The research applied non equivalent control grup design. The instrument used to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Other researchers, a study about the application of a Word Chain Game to teach vocabulary was also conducted by Ramadani et al (2020) who found that there is a substantial enhancement in the student's vocabulary after being educated using Word Chain Game. The findings of the previous study conducted by Ramadani et al (2020) also supported the findings of the current study which revealed that the implementation of the Word Chain Game might improve the student's vocabulary knowledge and mastery.…”
Section: The Teacher and Students' Perceptions Of The Implementation ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Other researchers, a study about the application of a Word Chain Game to teach vocabulary was also conducted by Ramadani et al (2020) who found that there is a substantial enhancement in the student's vocabulary after being educated using Word Chain Game. The findings of the previous study conducted by Ramadani et al (2020) also supported the findings of the current study which revealed that the implementation of the Word Chain Game might improve the student's vocabulary knowledge and mastery.…”
Section: The Teacher and Students' Perceptions Of The Implementation ...mentioning
confidence: 99%
“…However, there were some differences between the previous study that was initially conducted and this study. The previous study carried out by Ramadani et al (2020) did not investigate the teacher's steps as well as the students' perceptions of the application of the Word Chain Game in teaching and learning vocabulary. Furthermore, Ramadani et al (2020) focused on investigating the impact of the Word Chain Game in improving the student's vocabulary mastery.…”
Section: The Teacher and Students' Perceptions Of The Implementation ...mentioning
confidence: 99%
See 3 more Smart Citations